Screening Methods in Pharmacololgy. V.2 - Turner, Robert A.; Hebborn, Peter (USA : Academic Press, 1971)
Numerous methods often exist for screening a series of compounds for a given pharmacology activity.
Keywords: Pharmacololgy; Pharmacology, Screening Methods